Pengaruh Budaya Kerja dan Komunikasi terhadap Motivasi Kerja dan Kinerja Pegawai pada Badan Pusat Statistik Provinsi Sulawesi Tenggara - Eka Baktiar; Bakhtiar Abbas; Muh. Nur (Syntax Corporation Indonesia, 2024)
The purpose of this study is to investigate and analyze the impact of work culture and communication on employee motivation and performance at the Central Bureau of Statistics of Southeast Sulawesi Province, as well as understand the direct influence of work motivation on employee performance. The type of data used in this study is primary data which includes data related to respondents' statements on the variables of this study, namely work culture, communication, work motivation and employee performance at the Central Bureau of Statistics of Southeast Sulawesi Province. The results of the research findings, first, work culture has a positive and significant influence on work motivation and employee performance at the Central Bureau of Statistics of Southeast Sulawesi Province. The higher the work culture, the higher the motivation and performance of employees. Second, communication also has a positive and significant influence on work motivation and employee performance.